2019
DOI: 10.1111/sode.12431
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept as a mechanism through which parental psychological control impairs empathy development from adolescence to emerging adulthood

Abstract: We examined the relationship among perceived parental psychological control (PPC), self‐concept, and empathy, from adolescence to emerging adulthood. Child Development Project longitudinal data analyses indicate that, when adolescents notice PPC at age 13, they have poor self‐concept (less competence) at age 16, and they show less empathic concern (EC) toward others at age 24. The indirect effects of self‐concept at age 16 are significant for EC, but not for perspective taking (PT). Moreover, perceived PPC at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 74 publications
4
22
0
3
Order By: Relevance
“…Based on previous studies showing that men are more avoidant than women (Schmitt, 2003), and women are more anxious than men (Turner, 1991), boys may become more avoidant than girls and girls more anxious than boys. On the other hand, several studies have reported PPC's negative developmental outcomes regardless of the gender of the adolescent (Choe et al., 2019; Soenens & Vansteenkiste, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies showing that men are more avoidant than women (Schmitt, 2003), and women are more anxious than men (Turner, 1991), boys may become more avoidant than girls and girls more anxious than boys. On the other hand, several studies have reported PPC's negative developmental outcomes regardless of the gender of the adolescent (Choe et al., 2019; Soenens & Vansteenkiste, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Parental psychological control (PPC) refers to a set of intrusive parenting techniques that emotionally manipulate children to obey their parents (Choe & Read, 2019). Intrusiveness and emotional manipulation differentiate PPC from other parenting constructs (Choe et al., 2019). Firstly, intrusiveness entails that parents try to change their children's minds for matters that do not warrant parental intervention related to children's personal domains such as preferences and privacy (Smetana & Daddis, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent perceptions of parental psychological control predicted empathy through their perceptions of balanced connectedness with parents ( Yoo, Feng, & Day, 2013 ). A recent study also suggested that adolescent perception of parental psychological control predicted lower empathic concern indirectly with self-concept as a mediator, and lower perspective taking directly in early emerging adulthood ( Choe, Lee, & Read, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the SDT, satisfaction of one's autonomy needs induces sense of wellbeing, which promotes people to be less preoccupied with their own frustrations ( Gagne, 2003 ; Ryan & Deci, 2000 ), while individuals under controlling parenting experienced much self-focused distressed feelings, leaving not enough psychological resources available to care for others in empathic ways. In addition, those under psychological control have been inevitably deprived of opportunities to identify and understand their own emotions, leading to difficulties in developing perspective taking capabilities ( Choe et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%